The terrorist's dilemma managing violent covert organizations - Shapiro, Jacob N. (Princeton University Press, 2013)
How do terrorist groups control their members? Do the tools groups use to monitor their operatives and enforce discipline create security vulnerabilities that governments can exploit? This title examines the great variation in how terrorist groups are structured.